Implementasi Kebijakan Manfaat Jaminan Hari Tua di Indonesia (Jurnal Bina Praja, 2019)
Old-Age Insurance (JHT), which is intended for workers entering the old age, is now widely claimed when workers are still in their early age discussing the implementation of the policy on benefits of Old Age Insurance (JHT) in Indonesia. This study discusses the implementation of policies on benefits of Old Age Insurance (JHT) in Indonesia. JHT is a program in the form of giving cash when participants enter retirement age. In its implementation, there are several obstacles, namely many participants who took the benefits of JHT at a young age. This has led to a shift in the philosophy of JHT as well as the existence of companies that register good programs, wages and labor. The purpose of this study is to analyze the implementation of the JHT benefit policy in Indonesia and what determines the success of implementing the JHT benefit policy. This study used a descriptive qualitative approach with data collection techniques through in-depth interviews and literature studies. In-depth interviews were conducted with several informants including the government, BPJS Employment, participants and employers as well as NGOs. The results of this study, namely the implementation of the JHT benefit policy in Indonesia goes well despite disharmony of regulations and the successful implementation of the JHT benefit policy in Indonesia is strongly influenced by various things including the content and context of the policy itself and compliance with implementers and factual sociological conditions of the community. The conclusion is that implementation is going well even though it still faces both regulatory and compliance constraints, so it needs to be revised PP 60 in 2015, the existence of unemployment benefits so that it does not interfere with JHT and innovative performance is needed from BPJS Ketenagakerjaan.